Synergistic Effect of MC-LR and C-Terminal Truncated HBx on HepG2 Cells and Their Effects on PP2A Mediated Downstream Target of MAPK Signaling Pathway - Xiao, Chanchan; Mei, Fanbiao; Ren, Guanhua; Long, Long; Chen, Maojian; Fang, Xiang; Li, Jilin; Li, Kezhi; Tang, Yanping; Huang, Tianren; Deng, Wei (Frontiers in Genetics, 2020)
C-terminally truncated hepatitis B virus (HBV) X (ctHBx) infection, exposure of microcystins-LR ( MC-LR ) could lead to human hepatitis and liver cancer , but the exact mechanism of synergy between the two have not been fully clarified. In this work, a test of MC-LR exposure on containing ctHBx HepG2 cells at 0-10 M for 3-24 h. The western blot assay result showed that MC-LR entered ctHBx cells in a time-dependent pattern. We investigated the function of MC-LR and ctHBx (HBxΔ4 and HBxΔ32) on HepG2 cells using molecular biology approaches, including enzyme-linked immunosorbent assay(Elisa), colony formation, scratch wounding, transwell and flow cytometry assays, and found that MC-LR and ctHBx synergistically inhibited the activity of intracellular PP2A, and significantly enhanced the proliferation, migration, invasion and colony formation capability of HepG2 cells. In addition, MC-LR and HBxΔ32 activated the MEK/ERK/JNK/p38 MAPK signaling pathway to regulate cell viability by affecting the expression of cyclin-related proteins, including p53, cdc25C and cdc2. Taken together, our ﬁndings revealed the essential significance of the MC-LR and ctHBx PP2A/MAPK/p53,cdc25C and cdc2 axis in the formation and development of HCC and identified MC-LR and ctHBx as potential causal factors of hepatocarcinogenesis.